Gorgonians Are Foundation Species on Sponge-Dominated Mesophotic Coral Reefs in the Caribbean - Slattery, Marc; Lesser, Michael P. (Frontiers in Marine Science, 2021)
Foundation species [FS] regulate ecological processes within communities often facilitating biodiversity and habitat complexity. Typically FS are dominant structure-forming taxa; but less dominant taxa having disproportionate ecological impacts to the community can also be FS. Mesophotic coral ecosystems [MCEs] are deep ( 30-150 m) fore-reef communities often dominated by structure-forming sponges. Despite the potential competitive advantage of sponges on MCEs, gorgonians are also common constituents of these deep reefs. Data from the Bahamas demonstrate increased biodiversity and densities of sponges on deep reefs with gorgonians relative to reefs without these species. Drawing upon fifteen years of field surveys at five sites in the Caribbean basin we assessed in situ interactions between gorgonians and sponges to quantify outcomes consistent with competition (i.e., tissue necrosis and overgrowth). We also examined recruitment patterns near gorgonians to assess their role in facilitating MCE biodiversity. Our results indicate that live gorgonians, Antillogorgia bipinnata and Ellisella elongata, facilitate biodiverse recruitment into MCEs, indicating that this process is governed by more than passive hydrodynamics. These gorgonians were effective competitors against a variety of sponges, and two allelochemicals produced by E. elongata were mechanistically important in interactions with other species. Collectively, these data indicate that these gorgonians exhibit both positive and negative ecological interactions (i.e., facilitation and competition, respectively) with sponges. Thus, these gorgonians are FS of MCE communities within the Caribbean basin that displays several traits contributing to the ecological structure of these understudied communities.